There will come a darkness - Pool, Katy Rose (Henry Holt and Company, 2019)
The Age of Darkness approaches. Who will stop it... or unleash it? For generations, the Seven Prophets guided humanity. Using their visions of the future, they ended wars and united nations-- until they disappeared a hundred years ago. All they left behind was one final prophecy, foretelling an Age of Darkness and the birth of a new Prophet who could be the world's salvation-- or the cause of its destruction. Will it be a prince exiled from his kingdom? A ruthless killer known as the Pale Hand? A once-faithful leader torn between his duty and his heart? A reckless gambler with the power to find anything or anyone? Or a dying girl on the verge of giving up? -- adapted from jacket
Maps on endpapers
Series numeration from Goodreads.com
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Fantastischer Roman; Prophet; Weissagung; Prophecies / Juvenile fiction; Prophets / Juvenile fiction; Imaginary wars and battles / Juvenile fiction; Prophecies / Fiction; Fantasy; Imaginary wars and battles; Prophecies; Prophets; Juvenile works; Young adult fiction; Fantasy fiction; Fiction; Novels; Young adult works; Jugendbuch